Three-Dimensional Electrochemical Axial Lithography on Si Micro- and Nanowire Arrays - Rey, Marcel; Wendisch, Jan Fedja; Vogel, Nicolas; Diwald, Oliver; Bourret, Gilles Remi; Saller, Michael; Eadie, Alex; Reyer, Andreas; Musso, Maurizio (Nano Letters, 2018)
A templated electrochemical technique for patterning macroscopic arrays of single-crystalline Si micro- and nanowires with feature dimensions down to 5 nm is reported. This technique, termed three-dimensional electrochemical axial lithography (3DEAL), allows the design and parallel fabrication of hybrid silicon nanowire arrays decorated with complex metal nano-ring architectures in a flexible and modular approach. While conventional templated approaches are based on the direct replication of a template, our method can be used to perform high-resolution lithography on pre-existing nanostructures. This is made possible by the synthesis of a porous template with tunable dimensions that guides the deposition of well-defined metallic shells around the Si wires. The synthesis of a variety of ring architectures composed of different metals (Au, Ag, Fe, and Ni) with controlled sequence, height, and position along the wire is demonstrated for both straight and kinked wires. We observe a strong enhancement of the Raman signal for arrays of Si nanowires decorated with multiple gold rings due to the plasmonic hot spots created in these tailored architectures. The uniformity of the fabrication method is evidenced by a homogeneous increase in the Raman signal throughout the macroscopic sample. This demonstrates the reliability of the method for engineering plasmonic fields in three dimensions within Si wire array
Keywords: lithography; nano-rings; surface-enhanced Raman spectroscopy; plasmonics; Si nanowires